Sustainable Development Model for Three Small Communities in Costa Rica - Chassoul-Acosta, María José (2018)
As an alternative solution to economic, social and environmental problems in rural communities, this article proposes a model of sustainable endogenous rural development (DRES), focused on the management of waste employing eco-technologies and the generation of productive activities. The DRES is seen as an entrepreneurial and innovative process that allows the local community to improve their living conditions by establishing economic and socio-cultural activities using, basically, their own resources, but with the necessary openness to modify and integrate external knowledge. It includes economic growth and development, social welfare and the conservation of the natural environment. In this model, the improvement of the living condition has been achieved through the use of the capacities that allow the use of the resources available in the area.